131k views
3 votes
Using the Quotient Rule, use the Quotient Rule to find the derivative of the function.

Using the Quotient Rule, use the Quotient Rule to find the derivative of the function-example-1
User Jethar
by
5.1k points

2 Answers

3 votes

To find the derivative of
f(x) = (x^2)/(2√(x) + 1) using the Quotient Rule, calculate the derivatives of the numerator and the denominator separately, then apply the rule to obtain the derivative of the function.

Step-by-step explanation:

Using the Quotient Rule to find the derivative of the function
f(x) = (x^2)/(2√(x) + 1), we need to define the numerator as
u = x^2 and the denominator as
v = 2√(x) + 1. The Quotient Rule states that the derivative of a function in the form of u/v is given by
(v(u') - u(v')) / v^2. So, calculate the derivatives u' = 2x and
v' = (2)/(2√(x)) (using the chain rule and power rule for v'). Substituting these into the Quotient Rule formula gives the derivative of the function.

Firstly,

u' = 2x

Secondly,
v' = 1/√(x)

Thus, the derivative of f(x) becomes:


f'(x) = ((2√(x) + 1)(2x) - (x^2)(1/√(x)))/((2√(x) + 1)^2). This simplifies to give the final expression for the derivative after combining like terms and simplifying the fraction.

User Nitesh Kothari
by
4.7k points
1 vote

In calculus, the quotient rule is a method of finding the derivative of a function that is the ratio of two differentiable functions. This rule is given by the following expression:


((f)/(g))^(\prime)=(f^(\prime)g-fg^(\prime))/(g^2)

Applying this rule in our problem, we have:


\begin{gathered} f^(\prime)(x)=((x^2)^(\prime)(2√(x)+1)-(x^2)(2√(x)+1)^(\prime))/((2√(x)+1)^2) \\ \\ =((2x)(2√(x)+1)-(x^2)(2\cdot(1)/(2)(1)/(√(x))))/(4x+4√(x)+1) \\ \\ =(4x√(x)+2x-x√(x))/(4x+4√(x)+1) \\ \\ =(3x√(x)+2x)/(4x+4√(x)+1) \end{gathered}

User Danny Kirchmeier
by
5.3k points